2014
DOI: 10.1098/rstb.2013.0160
|View full text |Cite
|
Sign up to set email alerts
|

Lack of the presynaptic RhoGAP protein oligophrenin1 leads to cognitive disabilities through dysregulation of the cAMP/PKA signalling pathway

Abstract: Loss-of-function mutations in the gene encoding for the RhoGAP protein of oligophrenin-1 (OPHN1) lead to cognitive disabilities (CDs) in humans, yet the underlying mechanisms are not known. Here, we show that in mice constitutive lack of Ophn1 is associated with dysregulation of the cyclic adenosine monophosphate/phosphate kinase A (cAMP/PKA) signalling pathway in a brain-area-specific manner. Consistent with a key role of cAMP/PKA signalling in regulating presynaptic function and plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 58 publications
1
40
0
Order By: Relevance
“…We performed a rescue experiment by treatment with the clinically approved ROCK/PKA inhibitor fasudil (Khelfaoui et al, 2014, Meziane et al, 2016) and assessed whether this pharmacological strategy was able to restore the impairments in hippocampal neurogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…We performed a rescue experiment by treatment with the clinically approved ROCK/PKA inhibitor fasudil (Khelfaoui et al, 2014, Meziane et al, 2016) and assessed whether this pharmacological strategy was able to restore the impairments in hippocampal neurogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, similar to the suppression of spine organizational defects that are induced by oligophrenin1 loss-offunction (Govek et al, 2004), the LTD effects mediated by loss of oligophrenin1 could also be fully overcome with the inhibition of ROCK with Y-27632 (Khelfaoui et al, 2009). Because any presynaptic defects could also be alleviated with the administration of the PKA and RhoA-ROCK pathway inhibitor Fasudil (Khelfaoui et al, 2013), it appears that in all cases studied thus far, the observed oligophrenin1-knockout phenotypes in fact reflect a misregulation of signaling pathways rather than functions of oligophrenin1 as a membrane-shaping factor (Fig. 3C).…”
Section: Control By Signalingmentioning
confidence: 96%
“…Such changes involve alterations in synaptic strength at sensory thalamic 19 or cortical afferents 17 to BLA principal neurons, BLA inputs onto intercalated cells 88 or onto defined subtypes of CEA neurons 44 . Moreover, recent evidence from mouse genetic models for psychiatric conditions associated with anxi ety phenotypes has identified specific deficits in the function and plasticity of excitatory inputs to the amygdala and in the function of local inhibitory circuits [89][90][91][92] . In future studies, it will be important to address the cellular and synaptic specificity of diseaseassociated functional changes and to investigate whether such changes are cause or consequence in the pathophysiological processes mediating pro gression of anxiety disorders.…”
Section: Disease-associated Synaptic Plasticitymentioning
confidence: 99%